Implementação e avaliação da usabilidade de um aplicativo para o ensino de Libras - Pacheco, Jeandson Gonçalves (Brasil, 2024)
This project highlights the importance of social inclusion for disabled people and proposes the development of a mobile application for teaching Libras for Elementary 1 students. The objective is promoting diversification between classes and provide equal educational opportunities. The methodology includes a bibliographical survey to theoretical foundation, implementation based on the Waterfall Model and usability evaluation by pedagogues and teachers. The application aims to disseminate knowledge in Libras, contributing to greater understanding and respect for People with Hearing and Speech Impairments. It is concluded that the Libras application presented demonstrated a high approval rate, with 97% of participants recommending its implementation in classrooms. These results highlight the crucial importance of developing accessible educational tools to promote the inclusion of deaf people, thus ensuring equal opportunities and access to knowledge.